2017
DOI: 10.1111/ejh.12932
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin receptor agonist switch in adult primary immune thrombocytopenia patients: A retrospective collaborative survey involving 4 Spanish centres

Abstract: TPO-RA switching is a feasible strategy in different scenarios with high probability of success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
(46 reference statements)
1
17
0
Order By: Relevance
“…Some patients failing to respond to 1 TPO-RA may respond if switched to another TPO-RA (evidence levels IIb, III). 138,148,210,211 If not already done, splenectomy can also be reconsidered, as can searching for an accessory spleen. 212 In patients failing 1 medical therapy, changing to another medical treatment may be successful.…”
Section: Treatment Options For Adults Failing Multiple Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some patients failing to respond to 1 TPO-RA may respond if switched to another TPO-RA (evidence levels IIb, III). 138,148,210,211 If not already done, splenectomy can also be reconsidered, as can searching for an accessory spleen. 212 In patients failing 1 medical therapy, changing to another medical treatment may be successful.…”
Section: Treatment Options For Adults Failing Multiple Therapiesmentioning
confidence: 99%
“…New data have shown that switching from 1 TPO-RA to another, as well as sequential therapy, has a positive effect on response and on tolerability (evidence levels IIb, III). 138,148,210 Switching was shown to be effective in 50% to 80% of patients, resulting in eradication of platelet fluctuation in 54% of patients and resolution of AEs in all (evidence level IIb). 138 Another study showed that switching from romiplostim to eltrombopag led to 100% response rates, but switching from eltrombopag to romiplostim led to 66% response rates, when patients switched as a result of inefficacy of the first treatment.…”
Section: Treatment Options For Adults Failing Multiple Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 18 journal publications that reported retrospective findings in 401 patients with ITP who switched their TPO-RA therapy (Table 1). 2138 In a pooled analysis of these studies, lack of efficacy was identified as the primary reason for switching in 58% of patients (172/295). Non-efficacy-related reasons for switching included adverse events (AEs), patient preference, and platelet count fluctuations.…”
Section: Switching: Clinical Datamentioning
confidence: 99%
“…Importantly, a high response rate (65% [72/111]) and improved platelet counts were observed even if switching was due to lack of efficacy with the first TPO-RA. 2138…”
Section: Switching: Clinical Datamentioning
confidence: 99%